Chinese pangolins facilitate ecological restoration in burned forest sites by burrowing - Song Sun; Sheng Zhang; Fei Wu; Yuanwen Kuang; Yaqian Zhang; Hongliang Dou; Haiyang Gao; Ying Wang; Jinzhen Yang; Jingxin Wang; Yan Hua (Global Ecology and Conservation)
Ecosystem engineers are a critical driver of material cycling and energy flow in degraded or damaged ecosystems, and they are considered to be keystone species for ecological restoration. Despite their importance, there are relatively few studies that quantify the roles of ecosystem engineers during ecological restoration. In this study, the influence of excavation by Chinese pangolin (Manis pentadactyla) on biological processes during the restoration in burned forest sites in subtropical China were assessed. Results showed that plant species preferentially colonized burrow habitats and animal species intensively utilized burrow resources, benefiting the restoration of biodiversity in burned forest habitats. One year following forest fire, the network complexity and stability of plants and animals in burned habitats with burrows were significantly higher than those without burrows. The significantly positive associations between animals, especially birds, and multiple plant species suggested that the burrow utilization by animals accelerate the ecological processes of plant seed dispersal from fire-free to burrow habitats, and from burrow habitats to burned habitats without burrows. These findings imply that pangolin burrows serve as hubs for multi-species coexistence and accelerate the biodiversity restoration of burned forests. Excavation by ecosystem engineers, represented here by Chinese pangolins, exhibits important implications for ecological restoration of fire-burned forest ecosystems.